A comparative laboratory investigation into the role of geosynthetics in the initial swell control of an expansive soil - James, Jijo; Vijayasimhan, Sivapriva; Srinivasan, Hemavathi; Arulselvan, Javasri; Purushothaman, Sathya; Paramasivam, Murali (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Volume change in expansive soils due to the intervention of water causes swell. A laboratory investigation using two different geosynthetic materials was designed to minimise the swell characteristics. The influence of three parameters, being geosynthetic material [Secutex (ST) and Combigrid (CG)], orientation (horizontal and vertical), and number of layers (1, 2, and 3) on the swell of an expansive soil was studied to better understand the potential for geosynthetics in swell control.
Keywords: well of soil; expansive soil; volume change in soils; geosynthetic materials; layering; comparative investigation; pęknięcie; gleba; zmiana objętości; materiały geosyntetyczne; warstwy; badania porównawcze